Illustrated Montreal, the Metropolis of Canada. Its Romantic History, its Beautiful Scenery, its Grand Institutions, its Present Greatness, its Future Splendour. 1892-1893 (John McConniff, 1893)

Notice sur les écoles relevant du bureau des commissaires catholiques romains de la cité de Montréal (Canada) (s.é., 1893)
Keywords: Commission des écoles catholiques de Montréal

Notices historiques sur l'Institution catholique des sourds-muets pour la province de Québec dirigée par les Clercs de Saint-Viateur, Mile-End, Montréal (Imprimerie de l'Institution des sourds-muets, 1893)
Keywords: Clercs de Saint-Viateur; Communautés religieuses; Institution des sourds-muets; Sourds

Semi-Centennial Report of the Montreal Board of Trade. Sketches of the Growth of the City of Montreal from its Foundation, Statistics of Progress and Report of the Council for the Year Ending 31st December 1892 (Montreal Board of Trade, 1893)
Keywords: Montreal Board of Trade

L'église de St-François D'Assise de la Longue-Pointe - Bellay, A. (Revue canadienne, 1893)
Tome: 8
Keywords: Longue-Pointe; Saint-François-d'Assise (paroisse)

"ANOTE Kekon" - Cuoq, J.-A. (Mémoires et comptes rendus de la Société royale du Canada, 1893)
Keywords: Autochtones; Missions; Quéré de Tréguron, Maurice; Sulpiciens

Lake St. Louis, Old and New - Girouard, Désiré-H. (Poirier-Bessette, 1893)
Keywords: Saint-Louis (lac)

La cité de Saint-Cunégonde - Massicotte, E.-Z. (J. S. Houle, 1893)
Keywords: Sainte-Cunégonde

A Souvenir of the Opening of the New Building, One Thousand, Eight Hundred and Ninety-Three - Montreal Board Of Trade (Sabiston, 1893)
Keywords: Board of Trade

A Chronology of Montreal and of Canada from A.D. 1852 to A.D. 1893, Including Commercial Statistics, Historical Sketches of Commercial Corporations and Firms... - Terrill, Frederick William (Lovell, 1893)